CIVIL SOCIETY AND THE PROMOTION OF SOCIAL ENVIRONMENTAL RESPONSIBILITY - Qoʻchqarova Mastura (International Journal of Literature and Language Studies, 2026)
This article analyzes the role of civil society in fostering and promoting social environmental responsibility. Drawing on historical and contemporary theories, regional and national scholarship, as well as empirical studies, the impact of civil society institutions on environmental sustainability is examined. The article provides an in-depth discussion of the concept of social environmental responsibility, the participation of civil society organizations in environmental movements, and critical issues and debates in this field.